An Integrated Fuzzy Cognitive Map Approach in Modelling Factors of Management Quality in Banking Performance. Issue 3 (June 2020) - Chatterjee, Debmallya; Dhaigude, Amol S.
Based on the literature review and interviews with experts, this study identifies 11 factors that can effectively capture the management quality dimension of the capital adequacy, asset quality, management quality, earnings, liquidity and sensitivity to market risk (CAMELS) framework in evaluating the performance of banking institutions. It further models these factors using the integrated fuzzy cognitive map (FCM) and Matrice d'Impacts Croisés Multiplication Appliquée a UN Classement (MICMAC) approach. A scenario analysis is then conducted on the proposed model to study the interrelationships between these factors in a dynamic setting. The results suggest that of all the 11 factors identified, the 'internal control system' is the most influential factor in determining management soundness, whereas 'business per employee' is the most sensitive in which any impact on employee morale could impact business performance. The managerial and practical implications of our study are also discussed.